Zaspokajanie oczekiwań determinantem decyzji wyborczych zwolenników partii politycznych - Widera, Zbigniew (Political Preferences, 2014)
Meeting the needs of the voters is the primary responsibility of politicians. Political activity organize social life through the interaction of political institutions, which are the foundation of the democratic process of electing representatives mandated by society and legitimized in the elections. Well- conceived mission of serving the public is the foundation of a well-functioning relationship politician-voter. It is a way to meet the expectations that allows voters to build everyday life and faith in the future. It is worth to know the extent in which politicians meet the expectations of their constituents.